An Analysis of The Change of Meaning English Borrowing Word in Junior High School Indonesian Language Textbook - Putra, Reko Hary (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The use of vocabulary in textbooks can be used as a comparison because, the words are used formally, and the language is good because it is used to educate students to learn it. The purpose of this study is to find out the words absorbed into Indonesian in Indonesian textbooks, an important purpose in this study is to find out the types of absorbed words, and the changes in meaning that occur in words absorbed from English into English. Indonesian in Indonesian textbooks. This study uses a qualitative approach with the content analysis method. Absorption words are divided into three types, namely absorption words, mixed or hybrid absorption words, and absorption transitions/translations. Theory of meaning change from meaning expansion borrowing, meaning narrowing, meaning regeneration, and meaning degeneration. The results of the analysis showed that twenty-five absorbed words that had types, 6 absorbed words, 19 words that were mixed types borrowed from English in the Indonesian textbook presented in this change of meaning were 4 for meaning narrowing, and 21 loan words had no meaning change. Loan word analysis in English to Indonesian is a way that can be used for students to know and learn vocabulary that learning English can be done in many different ways and places